Accounting Information Systems: A Bibliometric Analysis of Research Domains and Methods (2000–2026) - Loso Judijanto (West Science Accounting and Finance, 2026)
This study aims to map the intellectual structure, thematic evolution, and research trends in career adaptability and related domains through a comprehensive bibliometric analysis. Data were collected from the Scopus database, covering publications from 2000 to 2026, and analyzed using VOSviewer to generate co-occurrence, overlay, and density visualizations. The findings reveal that career adaptability has emerged as a central and integrative concept, connecting key research domains such as psychological factors, career guidance, employability, and educational systems. The network analysis identifies several major clusters, reflecting the multidisciplinary nature of the field, while the overlay visualization indicates a clear shift from early theoretical foundations—such as self-efficacy and career construction—toward more applied themes including employment readiness, professional development, and learning systems. Additionally, the density analysis highlights a strong concentration of research around core topics, alongside emerging but underexplored areas, particularly in the integration of digital technologies and innovative learning environments. The results suggest that the field is evolving toward a more practical and outcome-oriented direction, driven by global labor market changes and technological advancements. This study contributes by providing a systematic overview of research domains and methodological trends, offering valuable insights for scholars and practitioners, and identifying future research opportunities to enhance the relevance and impact of career development studies in a rapidly changing world.